2021
DOI: 10.1093/heapro/daab209
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy and acceptance: an examination of predictive factors in COVID-19 vaccination in Saudi Arabia

Abstract: Summary Vaccine hesitancy is a global health issue and can be affected by several variables. We explored the predictive factors and causes of vaccine hesitancy among adults in Saudi Arabia. An online survey method with multiple regression analysis was used to identify factors predicting of vaccine hesitancy in 558 adults (46.24% women and 53.76% men). The prevalence of vaccine hesitancy is 20.6%, with higher rates among females, young people and single people. About 70% of the participants belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…The present study showed that about 70% of the participants reported a moderate to high acceptance of the COVID-19 vaccine. Several other Saudi studies were almost in line with our results, which showed that 62-71% of Saudi citizens and Saudi residents have a good acceptance of COVID-19 vaccines (Narapureddy et al 2021;Alqahtani 2021;Alshahrani et al 2021;Maqsood et al 2022;Al-Mohaithef and Padhi 2020;Fadhel 2021;Yahia et al 2021;Elharake et al 2021). However, Khalafalla et al reported that 83.6% of Jazan University students were willing to take the COVID-19 vaccine, which was described as having a high acceptance rate compared to most studies conducted in Saudi Arabia (Khalafalla et al 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study showed that about 70% of the participants reported a moderate to high acceptance of the COVID-19 vaccine. Several other Saudi studies were almost in line with our results, which showed that 62-71% of Saudi citizens and Saudi residents have a good acceptance of COVID-19 vaccines (Narapureddy et al 2021;Alqahtani 2021;Alshahrani et al 2021;Maqsood et al 2022;Al-Mohaithef and Padhi 2020;Fadhel 2021;Yahia et al 2021;Elharake et al 2021). However, Khalafalla et al reported that 83.6% of Jazan University students were willing to take the COVID-19 vaccine, which was described as having a high acceptance rate compared to most studies conducted in Saudi Arabia (Khalafalla et al 2022).…”
Section: Discussionsupporting
confidence: 91%
“…While a survey in Bangladesh found that about a quarter of participants thought that COVID-19 was safe, only 60% were willing to be vaccinated, and about two-thirds will recommend it to family and friends (Islam et al 2021). It is believed that misinformation and lack of data on the seriousness of incidence and mortality of COVID-19 disease may reduce concerns about vaccine acceptability (Geoghegan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, low anti-SARS-CoV-2 vaccination levels are currently associated with social resistance partly based on beliefs in hidden social and political forces that allegedly pursue their own mainly pernicious goals through the ostensible struggle with the COVID-19 pandemic [ 27 , 28 , 29 ]. COVID-19-related conspiracy theories are known to have made serious obstacles in various countries with quite different cultural heritages, religions, ethnic compositions, economic developments, and levels of income: in Canada [ 30 ], Croatia [ 31 ], Germany [ 32 , 33 ], Ghana [ 34 ], India [ 35 ], Jordan [ 36 ], Kuwait [ 37 ], Pakistan [ 38 ], People’s Republic of China [ 39 ], Poland [ 40 ], Saudi Arabia [ 41 ], Turkey [ 42 ], Ukraine [ 43 ], the United Kingdom [ 44 , 45 ], and the United States [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of our cohort of participating parents received at least 2 doses of the COVID-19 vaccine, while only 3.2% did not receive any dose. That high rate of vaccine acceptance points to healthy parental attitudes toward vaccination, and studies from the adult Saudi population have shown COVID-19 vaccine acceptance rates ranging between 52–71% [ 13 , 21 ]. However, COVID-19 vaccination efforts in KSA for children have been affected by parental acceptance and hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that at the end of 2021, 50% of the World Health Organization (WHO) member states achieved a target of 40% immunization, and this rate is <10% in low-income countries [ 12 ]. Studies from KSA have shown an acceptance rate for COVID-19 vaccine among the general population between 40.7–71% [ 13 , 14 ]. The rate was 70% among healthcare workers in the KSA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%